The glycan-binding protein galectin-1 controls survival of epithelial cells along the crypt-villus axis of small intestine - Muglia, Cecilia Isabel (2011)
Abstract: Intestinal epithelial cells serve as mechanical barriers and active components of the mucosal immune system. These cells migrate from the crypt to the tip of the villus, where different stimuli can differentially affect their survival. Here we investigated, using in vitro and in vivo strategies, the role of galectin-1 (Gal-1), an evolutionarily conserved glycan-binding protein, in modulating the survival of human and mouse enterocytes. Both Gal-1 and its specific glyco-receptors were broadly expressed in small bowel enterocytes. Exogenous Gal-1 reduced the viability of enterocytes through apoptotic mechanisms involving activation of both caspase and mitochondrial pathways. Consistent with these findings, apoptotic cells were mainly detected at the tip of the villi, following administration of Gal-1. Moreover, Gal-1-deficient (Lgals-1-) mice showed longer villi compared with their wild-type counterparts in vivo. In an experimental model of starvation, fasted wild-type mice displayed reduced villi and lower intestinal weight compared with Lgals-1- mutant mice, an effect reflected by changes in the frequency of enterocyte apoptosis. Of note, human small bowel enterocytes were also prone to this pro-apoptotic effect. Thus, Gal-1 is broadly expressed in mucosal tissue and influences the viability of human and mouse enterocytes, an effect which might influence the migration of these cells from the crypt, the integrity of the villus and the epithelial barrier function.